Higher Desolvation Energy Reduces Molecular Recognition in Multi-Drug Resistant HIV-1 Protease - Wang, Yong (MDPI, 2012)
Designing HIV-1 protease inhibitors that overcome drug-resistance is still a challenging task. In this study, four clinical isolates of multi-drug resistant HIV-1 proteases that exhibit resistance to all the US FDA-approved HIV-1 protease inhibitors and also reduce the substrate recognition ability were examined. A multi-drug resistant HIV-1 protease isolate, MDR 769, was co-crystallized with the p2/NC substrate and the mutated CA/p2 substrate, CA/p2 P1’F. Both substrates display different levels of molecular recognition by the wild-type and multi-drug resistant HIV-1 protease. From the crystal structures, only limited differences can be identified between the wild-type and multi-drug resistant protease. Therefore, a wild-type HIV-1 protease and four multi-drug resistant HIV-1 proteases in complex with the two peptides were modeled based on the crystal structures and examined during a 10 ns-molecular dynamics simulation. The simulation results reveal that the multi-drug resistant HIV-1 proteases require higher desolvation energy to form complexes with the peptides. This result suggests that the desolvation of the HIV-1 protease active site is an important step of protease-ligand complex formation as well as drug resistance. Therefore, desolvation energy could be considered as a parameter in the evaluation of future HIV-1 protease inhibitor candidates.